Food "buycott" as an ethical choice against mafia in Italy. Issue 4 (14th October 2019) - Rivaroli, Sergio; Ruggeri, Arianna; Spadoni, Roberta
Abstract : Purpose: As indicated in the Italian law (No. 109-1996), agri-food co-operatives can also play a role in combatting mafia-type systems by choosing to grow their food products in lands confiscated from mafia-type organisations. These food products provide individuals with a new opportunity to fight criminal organisations on the marketplace. The purpose of this study is to explore how people react to a social marketing initiative devoted to promoting food "buycotting" to counteract mafia-type organisations in Italy. Design/methodology/approach: The data were obtained from a convenience sample of 339 Italians, and the study adopted a model inspired by the general theory of marketing ethics. A structural equation model was applied to estimate both the parameter and coefficient functions. Findings: Individuals recognise the ethical value of "buycotting". However, they perceive this form of critical choice as not yet being fully effective in counteracting mafia-type systems in Italy. Practical implications: The results suggest that promotional and psychological approaches from marketing literature can be effectively used to influence the consumer's ethical judgement by selectively communicating and emphasising the benefits of the critical consumption investigated. Originality/value: This is one of the first studies to address consumers' ethical judgments and their reactions towards buycotting food as a critical choice to reward socially responsible corporations.